2006
DOI: 10.3171/jns.2006.105.3.465
|View full text |Cite
|
Sign up to set email alerts
|

Tako-tsubo cardiomyopathy: reversible heart failure with favorable outcome in patients with intracerebral hemorrhage

Abstract: In patients with intracerebal hemorrhage, cardiac dysfunction is a common phenomenon. Tako-tsubo cardiomyopathy is characterized by complete reversibility and therefore may constitute an entity with a favorable outcome. In this case report the authors describe a previously healthy 23-year-old man with no history of cardiac disease who suffered a severe fourth ventricular hemorrhage due to an angioma of the vermis cerebelli. After emergency surgery, progressive tachycardia, fibrillation, and electromechanical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Dysfunction of left ventricular regional wall motion occurs in approximately 18% of SAH patients,20 and takotsubo cardiomyopathy was identified on ECG and imaging studies in 8 of 661 (1.2%) SAH patients 10. At least one patient with intracerebral hemorrhage was reported to have experienced development of takotsubo cardiomyopathy 21. This incidence of takotsubo cardiomyopathy in ischemic stroke patients (1.2%) suggests that the cardiomyopathy is as important a complication of ischemic stroke as of SAH.…”
Section: Discussionmentioning
confidence: 98%
“…Dysfunction of left ventricular regional wall motion occurs in approximately 18% of SAH patients,20 and takotsubo cardiomyopathy was identified on ECG and imaging studies in 8 of 661 (1.2%) SAH patients 10. At least one patient with intracerebral hemorrhage was reported to have experienced development of takotsubo cardiomyopathy 21. This incidence of takotsubo cardiomyopathy in ischemic stroke patients (1.2%) suggests that the cardiomyopathy is as important a complication of ischemic stroke as of SAH.…”
Section: Discussionmentioning
confidence: 98%
“…This assumption is also supported by our data, showing a higher frequency of diabetes mellitus, hypercholesterolemia, smoking and coronary artery disease in ischemic stroke patients as opposed to ICH patients (data not shown). In contrast, neuronally induced autonomic cardiac dysfunction, as reported in subarachnoid hemorrhage and ICH for stress-induced cardiomyopathy, might be a rarer event [18,19,20]. Another study from Hays and Diringer [21] identified elevated troponin I levels to be independently associated with in-hospital mortality after ICH; however, only 3 out of 90 deaths were related to cardiac events.…”
Section: Discussionmentioning
confidence: 99%
“…TTS following an ICH has been reported in nine cases so far [29,97,[120][121][122][123][124][125][126]. In four of these cases TTS was associated with cerebellar hemorrhage [29,97,125,126].…”
Section: Intra-cerebral Hemorrhage (Ich)mentioning
confidence: 92%